Pengaruh Program Kelas Bahasa Arab pada Lembaga CELAD terhadap Penguasaan Mufrodat (Kosa Kata) Mahasiswa - Ahmad, Mawardi; Akzam, Ismail; Yunita, Yenni (UIR Press, 2019)
This study was motivated by the problem of mastering Arabic in the Faculty of Islamic studies (FAI), Islamic university of Riau (UIR). This problem focused on the students’ quality and learning interest of FAI UIR on language mastery, both Arabic and English. This foreign language or second language mastery program such as Arabic or English is made in the form of language classes. Language classes are initially unattended by a special institution such as a language center now under the supervision of the FAI UIR language center, the forerunner of the UIR language center called CELAD (Center for Languages ​​and Academic Development). Formulation The problem of this research is how the implementation of Arabic learning and the influence of the Arabic language class on the mastery of student learning in the Faculty of Islamic Studies UIR. The purpose of this study was to find out the implementation of Arabic learning and the influence of the Arabic language class on the mastery of student learning in the Faculty of Islamic studies. The type of this research is descriptive as well as qualitiative and quantitative research. The literature review used is language learning, the influence of the Arabic language class, and vocabulary mastery (al-mufradat). Then based on the results of the study using quantitative descriptive analysis, it found that the implementation of Arabic learning and the influence of the Arabic class on students’ vocabulary mastery of FAI UIR can be said to be